Perspective on the microbiological profile of pneumonia associated with mechanical ventilation in high complexity hospitals in Latin America - Rebellón Sánchez, David (2015)
The prevalence of infection is higher in hospitals of high complexity and is one of the most important causes of mortality worldwide. Ventilator associated pneumonia (VAP) is one of the most common infection and have one of the highest mortality rates of nosocomial infections. VAP is defined like a lung infection that develops 48 hours or more after tracheal intubation process without prior evidence of microbial incubation in the respiratory tract. Current evidence suggests that VAP is associated with increased mortality, prolonged Intensive Care Unit stay and higher hospitalization costs. The aim of this article is to describe the pathogenic characteristics and risk factors that impact on mortality and survival of patients who develop VAP in major hospitals in Latin America in order to facilitate decision-making by the treating physician in this disease.